Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

New evidence from hybrid ground-based gravity observations of a regional gravity increase in southern Tibet before 2015 - Lulu Jia; Shi Chen; Linhai Wang; Hongyan Lu; Mian Liu; Weimin Xu; Zhitang He; Zhaohui Chen; Jiancheng Han (Tectonophysics, 2026)

Discovery and implications of the Late Carboniferous Tasensu gabbro–gabbrodiorite–granodiorite–monzogranite bimodal intrusions in Xiwuqi, Inner Mongolia, China - Wenjing Yang; Tianshe Cheng; Xuebin Zhang; Xiangqian He; Guoping Wang; Xujiang Cheng; Linhai Wang; Lijun Guo; Xingfang Duo; Hongsheng Gao (Journal of Volcanology and Geothermal Research, 2026)

Selective growth of (5, 4) single-walled carbon nanotubes - Qianru Wu; Xueting Zhang; Hao An; Liu Qian; Linhai Li; Huaping Liu; Jiayang Zhang; Lili Zhang; Lianming Tong; Maoshuai He; Chang Liu; Feng Ding; et al. (Science Bulletin, 2025)

Gangue-based Cu/SSZ-13 zeolites with controllable Al distribution as robust selective catalytic reduction (SCR) catalysts - Tongrui Liu; Linying Wang; Linhai He; Huihui Chen; Dong Fan; Dali Zhu; Miao Yang; Peng Tian; Zhongmin Liu (Chemical Engineering Journal, 2025)

Yttrium-catalyzed growth of enriched (6, 4) and (6, 5) carbon nanotubes for their high-efficiency separation - Xuan Lv; Linhai Li; Zhaoyang Han; Qianru Wu; Fangfang Cheng; Mengyu Wang; Guodong Xu; Huaping Liu; Maoshuai He (Chemical Engineering Journal, 2025)

Effect of Interaction of ATG7 and Plasma Metal Concentrations on Cognitive Impairment in Rural China - Xu Tang; Jiejing Cao; Jiansheng Cai; Xiaoting Mo; Yanfei Wei; Kailian He; Zeyan Ye; Yu Jian Liang; Linhai Zhao; Lidong Qin; You Li; Jian Qin; et al. (Journal of Molecular Neuroscience, 2025)

Reconstructing the late Quaternary soil erosion and dust deposition dynamics in the southern Loess Plateau: Insights from Lake Luyanghu sedimentary records - Hongfei Zhao; Xin Zhou; Linhai Yang; Hao Long; Liangqing Cheng; Yonghao Yan; Jie Zhou; Qianli Sun; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2024)

Effects of KLF11 on Vascular Smooth Muscle Cells and its Underlying Mechanisms in Intracranial Aneurysm - Ke Yan; Jiarong Bian; Liang He; Bingwei Song; Linhai Shen; Yong Zhen (Biochemical Genetics, 2024)

Single-grain K-feldspar luminescence dating of the late Quaternary rapid decline in the largest Lake over the Tibetan Plateau - Hao Long; Jingran Zhang; Xiaoling Huang; Aimin Zhang; Na Yang; Mengying He; Linhai Yang (Quaternary Geochronology, 2024)

The implications of N6-methyladenosine (m6A) modification in esophageal carcinoma - Cheng He; Xiao Teng; Luming Wang; Miaoqi Ni; Linhai Zhu; Jiacong Liu; Wang Lv; Jian Hu (Molecular Biology Reports, 2023)
Esophageal carcinoma (EC) is always diagnosed at advanced stage and its the mortality rate remains high. The patients usually miss the best opportunity for treatment because of non-specific symptoms and the survival rates are low. N6-methyladenosine (m6A) the predominant modification in eukaryotic messenger RNA(mRNA), serves vital roles in numerous bioprocess. This chemical modification is dynamic, reversible and consists of three regulators: m6A methyltransferases (writers), demethylases (erasers) and m6A-binding proteins (readers). Recently, a growing number of evidences have indicated relationships between m6A and EC. Whereas, lacking of cognition about the molecular mechanism of m6A modification in esophageal carcinoma. We will focus on the biological function roles of m6A modification in the tumorigenesis and development of EC. Recent studies showed that immunotherapy had a positive impact on EC. The relationship between m6A and immunotherapy in EC deserves further research and discussion. We will also discuss the potential clinical applications regarding diagnosis, treatment and prognosis of m6A modification for EC and provide perspectives for further studies.

Quantifying the dynamic processes of soil erosion and lake sediment deposition in the Holocene in China - Hongfei Zhao; Yunhong Lin; Jie Zhou; Qianli Sun; Linhai Yang; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2023)

Body weight, CYP2C19, and P2Y12 receptor polymorphisms relate to clopidogrel resistance in a cohort of Chinese ischemic stroke patients with aspirin intolerance - Zhiqiang Li; Wanqing Dong; Daorong Yang; Linhai Sun; Xianjun He; Huanhuan Hu; Jianping Zhang; Chunyu Wang; Yulin Li; Ming Zhao; Yu Kong; Yan Wang (European Journal of Clinical Pharmacology, 2020)

Correction to: Reducing macrophage numbers alleviates temporomandibular joint ankylosis - Lu Zhao; E Xiao; Linhai He; Denghui Duan; Yang He; Shuo Chen; Yi Zhang; Yehua Gan (Cell and Tissue Research, 2020)

Reducing macrophage numbers alleviates temporomandibular joint ankylosis - Lu Zhao; E Xiao; Linhai He; Denghui Duan; Yang He; Shuo Chen; Yi Zhang; Yehua Gan (Cell and Tissue Research, 2020)

Identification of key genes relevant to the prognosis of ER-positive and ER-negative breast cancer based on a prognostic prediction system - Bin Xiao; Jianfeng Hang; Ting Lei; Yongyin He; Zhenzhan Kuang; Li Wang; Lidan Chen; Jia He; Weiyun Zhang; Yang Liao; Zhaohui Sun; Linhai Li (Molecular Biology Reports, 2019)